A genome‐wide identified risk variant for PTSD is a methylation quantitative trait locus and confers decreased cortical activation to fearful faces. Issue 5 (18th May 2015) - Almli, Lynn M.; Stevens, Jennifer S.; Smith, Alicia K.; Kilaru, Varun; Meng, Qian; Flory, Janine; Abu‐Amara, Duna; Hammamieh, Rasha; Yang, Ruoting; Mercer, Kristina B.; Binder, Elizabeth B.; Bradley, Bekh; et al.
Abstract : Genetic factors appear to be highly relevant to predicting differential risk for the development of post‐traumatic stress disorder (PTSD). In a discovery sample, we conducted a genome‐wide association study (GWAS) for PTSD using a small military cohort (Systems Biology PTSD Biomarkers Consortium; SBPBC, N = 147) that was designed as a case‐controlled sample of highly exposed, recently returning veterans with and without combat‐related PTSD. A genome‐wide significant single nucleotide polymorphism (SNP), rs717947, at chromosome 4p15 (N = 147, β = 31.34, P  = 1.28 × 10 −8 ) was found to associate with the gold‐standard diagnostic measure for PTSD (the Clinician Administered PTSD Scale). We conducted replication and follow‐up studies in an external sample, a larger urban community cohort (Grady Trauma Project, GTP, N = 2006), to determine the robustness and putative functionality of this risk variant. In the GTP replication sample, SNP rs717947 associated with PTSD diagnosis in females (N = 2006, P  = 0.005), but not males. SNP rs717947 was also found to be a methylation quantitative trait locus (meQTL) in the GTP replication sample (N = 157, P  = 0.002). Further, the risk allele of rs717947 was associated with decreased medial and dorsolateral cortical activation to fearful faces (N = 53, P  < 0.05) in the GTP replication sample. These data identify a genome‐wide significant polymorphism conferring risk for PTSD, which was associated with differential epigenetic regulation and with differential cortical responses to fear in a replication sample. These results may provide new insight into understanding genetic and epigenetic regulation of PTSD and intermediate phenotypes that contribute to this disorder. © 2015 Wiley Periodicals, Inc.